Electrocardiographic changes in therapeutic hypothermia - Rolfast, Corina L (BioMed Central, 2012)
INTRODUCTION: During therapeutic hypothermia (TH), electrocardiographic (ECG) abnormalities such as Osborn waves and/or ST-segment elevation have been described. However, the incidence and prognostic value of these ECG changes are uncertain given the small-scale studies that have been carried out to date. The aim of this study is to further evaluate the electrocardiographic changes during TH. METHODS: During a period of 3 years, 81 patients (age 63 ± 14 years) were included retrospectively. All patients underwent TH after being resuscitated. ECG registrations before, during and after TH were collected and analyzed. Patients were divided into two groups based on the presence or absence of transmural ischemia ST elevation on the first representative ECG upon arrival at the hospital (ST-segment elevation myocardial infarction (STEMI) and non-STEMI). RESULTS: A total of 243 ECGs were analyzed. During TH 24 patients (30%) had Osborn waves, which disappeared in 22 patients (92%) after regaining normal body temperature. The presence of Osborn waves was not associated with age, gender, average pH, electrolytes, or lactate levels and was not associated with excess in-hospital mortality. In 10 patients (12%, six non-STEMI patients) new STEMI was observed during TH, which disappeared after TH discontinuation. The STEMI group (44 patients) had significantly more Osborn waves during TH than the non-STEMI group (38.6% vs. 15.2%, odds ratio = 3.508; 95% confidence interval = 1.281 to 9.610). CONCLUSIONS: Hypothermia-induced Osborn waves are relatively common and are not associated with an unfavorable short-term outcome. TH is associated with ECG changes that may mimic STEMI.